The Fed takes on corporate credit risk: An analysis of the efficacy of the SMCCF - Simon Gilchrist; Bin Wei; Vivian Z. Yue; Egon Zakrajšek (Federal Reserve Bank of Boston, 2024)
This paper evaluates the efficacy of the Secondary Market Corporate Credit Facility, a program designed to stabilize the U.S. corporate bond market during the COVID-19 pandemic. The program announcements on March 23 and April 9, 2020, significantly reduced investment-grade credit spreads across the maturity spectrum-irrespective of the program's maturity-eligibility criterion-and ultimately restored the normal upward-sloping term structure of credit spreads. The Federal Reserve's actual purchases reduced credit spreads of eligible bonds 3 basis points more than those of ineligible bonds, a sizable effect given the modest volume of purchases. A calibrated variant of the preferred habit model shows that a "dash for cash"-a selloff of shorter-term lowest-risk investment-grade bonds-combined with a spike in the arbitrageurs' risk aversion, can account for the inversion of the investment-grade credit curve during the height of turmoil in the market. Consistent with the empirical findings, the Fed's announcements, by reducing risk aversion and alleviating market segmentation, helped restore the upward-sloping credit curve in the investment-grade segment of the market.
Keywords: E44; E58; G12; G14; 330; COVID-19; SMCCF; credit spreads; credit market support facilities; event study; purchase effects; preferred habitat